River modeling using hec-ras for Sungai Junjung / Muhammad Radzi A Rashid - A Rashid, Muhammad Radzi (Faculty of Civil Engineering, 2006)
Sungai Junjung is located in the district of Seberang Perai Tengah, Pulau Pinang and has catchment area of approximately 127 km² comprising of the main river and its tributes, Sg Macang Bubuk, Sg Cempedak, Sg Junjung Mati, Sg Batu Tiga ,Sg. Perangin and Sg. Tok Subuh. Despite being surrounded by an environment conducive to its development, the area is currently facing a setback arising mainly from lack of flood mitigation master plan. As a result, incidences of flash floods and water logging have become major prevalent problem affecting several areas. This study are to model the river by using HEC-RAS software for the flood mitigation along the course of Sg Junjung.. HEC-RAS model was used to perform one-dimensional (1D) hydraulic calculations for a full network of natural and constructed channels. To perform the hydraulic model using HEC-RAS, the required data were geometric data, flow data and the boundary conditions of the stream. All these data were needed to perform the calculation of hydraulic water surface. As a result, HEC-RAS model showed that the possibility of flood to occur the duration rainfall of 30 minutes for ARI 2,5,20,50, 100 years. Besides that the comparison between different Manning’s N also was made. Lastly the new proposed level that obtained hopefully will give to responsible party as a alternative way to solving this problem.